Updates and challenges in pancreatic cytopathology - Patrick Yang; Liying Han; Zhongren Zhou (Elsevier, 2024)
The World Health Organization (WHO) has recently introduced an international approach to standardize reporting of pancreaticobiliary cytopathology. The WHO Reporting system for Pancreaticobiliary Cytopathology (WHO system) introduces two distinct categories for non-invasive premalignant lesions of the ductal system, based on cytomorphological grading: "pancreatic neoplasm of low risk/grade" (PaN-low) and "pancreatic neoplasm of high risk/grade" (PaN-high). This reclassification aims to provide a more precise assessment of risks of malignancy (ROM) for different neoplastic categories. The WHO system focuses on the diagnostic categories, their associated ROM, and recommended management per category.Pancreatic neoplasms comprise various histological types, each displaying distinct background features that can assist in the diagnostic process. Recognizing background features like mucin background, necrotic background, desmoplastic stroma, cancer-associated fibroblasts, and stromal fragments presents notable challenges. Certain background features may overlap across histological types.In this review, we present a summary of the key updates in the WHO system and highlight diagnostic challenges associated with background features.